1999
DOI: 10.1046/j.1365-2516.1999.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint replacement for a spontaneously ankylosed hip in a haemophilic patient

Abstract: A cemented Charnley total hip prosthesis was implanted in a 48-year-old man with mild haemophilia (factor VIII 4 IU dL-1) in his right spontaneously ankylosed hip. At the time of surgery he was anti-HCV positive, anti-HIV negative, and no circulating inhibitors were encountered. The indication for surgery was long-lasting intractable low back and ipsilateral knee pain. At 4-month follow-up, relief of pain was achieved as well as correction of limb-length discrepancy, with a good result according to the Mayo Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The main indication is severe and intractable pain at the low back and at the ipsilateral knee. One conversion of a spontaneously ankylosed hip has been converted to a THA in an HIV-negative patient, with a satisfactory result [39].…”
Section: Aseptic Looseningmentioning
confidence: 99%
“…The main indication is severe and intractable pain at the low back and at the ipsilateral knee. One conversion of a spontaneously ankylosed hip has been converted to a THA in an HIV-negative patient, with a satisfactory result [39].…”
Section: Aseptic Looseningmentioning
confidence: 99%
“…Another suitable study was found, giving us a final yield of 20 articles. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Figure 1 outlines the literature search process.…”
Section: Databases Search Resultsmentioning
confidence: 99%
“…The main indication is severe and intractable pain at the low back and at the ipsilateral knee. One spontaneously ankylosed hip has been converted to a THA in a HIV-negative patient, with a satisfactory result [40].…”
Section: Total Hip Arthroplastymentioning
confidence: 99%
“…The results of 35 primary TKAs performed in 30 haemophilic patients between 1996 and 2005 (10year period) were reviewed retrospectively. The average age of patients was 31 years (range: [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and the average follow-up was 7.5 years (range: 1-10). Twenty-five patients had haemophilia A and five had haemophilia B.…”
Section: Authorõs Experience Regarding Tka In Haemophiliamentioning
confidence: 99%